The (in)justices of smart local energy systems: A systematic review, integrated framework, and future research agenda. (January 2022) - Knox, Stephen; Hannon, Matthew; Stewart, Fraser; Ford, Rebecca
Abstract: Smart technology alongside local energy systems are regularly considered critical for a low-carbon transition. More recently, a growing body of literature has started to examine the (in)justices that exist within energy systems and the impact this has on all people having equal access to safe, affordable, and sustainable energy. To date, little research has sought to synthesise the evidence base around whether smart local energy systems are an effective means of promoting energy justice. This paper presents a systematic literature review of 105 peer-reviewed articles, with a focus on understanding the antecedents of energy justice in local energy systems and the role smart technology can play in mitigating these (in)justices. We propose an integrated framework outlining our findings and discuss the implications for a future research agenda.